Effect of long-term and rapid thermal treatments on the formation of the aluminum – polysilicon interface - Pilipenka, Uladzimir A.; Kovalchuk, Natalya S.; Zhyhulin, Dmitry V.; Shestovski, Dmitry V.; Anishchik, Victor M.; Ponariadov, Vladimir V. (Journal of the Belarusian State University. Physics, 2023)
The influence of long-term and rapid thermal treatments on the formation of the aluminum – polysilicon interface on aluminum – polysilicon – silicon dioxide structures in order to study the ohmic contacts in the element base of integrated circuits are considered. The obtained structures were subjected to various thermal treatments: standard (long-term) thermal annealing (450 °С, 20 min, N2 environment) used to create ohmic contacts at the stage of integrated circuit manufacturing and rapid thermal annealing (450 °С, 7 s, Ar environment). It is established, that during long-term thermal treatment, polysilicon is completely dissolved in aluminum, followed by segregation in the form of separate acute-angled polysilicon conglomerates on the surface of silicon dioxide, which can lead to a complete failure of the integrated circuit. With rapid thermal treatment, this effect is not observed. Thus, when forming an ohmic aluminum – polysilicon contact at the stage of integrated circuit manufacturing, it is advisable to use rapid thermal treatment, which significantly reduces the dissolution of polysilicon in aluminum and thereby contributes to the formation of an ohmic contact.
Keywords: aluminum – polysilicon interface; ohmic contact; rapid thermal treatment; integrated circuit; scanning electron microscopy; energy dispersive microanalysis